Special Autonomy Fund as Implementation of Special Autonomy Policy Aceh - Febi Priska Litami; Achmad Lutfi (PT. Publikasiku Academic Solution, 2023)
The purpose of this study is to evaluate the implementation of the Special Autonomy Fund in Aceh, an initiative that stems from decentralization policy reform in Indonesia that aims to promote regional development and resolve armed conflicts in Aceh. Through the literature study method, this study investigates the evolution of special autonomy policies, starting from the enactment of Law No. 22/1999 and Law No. 25/1999, to the ratification of Law No. 11 of 2006 concerning the Government of Aceh, which marked the transition from centralist government to decentralization, giving Aceh broad autonomy in various aspects of local life. Analysis of the data shows that the allocation of the Special Autonomy Fund, which began in 2008 and will continue until 2027, fluctuated, with an increase over the first 15 years followed by an anticipated gradual decline. The results of the study confirm that the Government of Aceh has succeeded in realizing most of the allocated funds, with emphasis on infrastructure, economy, poverty reduction, as well as education, social, and health, illustrating Aceh's effectiveness in using funds for development and community welfare. The study concludes that the Special Autonomy Fund has become an effective policy instrument in supporting Aceh's regional autonomy and sustainable development. These findings provide important implications for policymaking in other regions with similar uniqueness in Indonesia, offering insight into how asymmetric decentralization can be used as a tool for managing diversity within a unitary state.